LETTERS FROM INDIA - Ramsay, Susan, 1837-1898. ([S.l.])
1 online resource
Keywords: This fascinating volume reproduces the letters and journal of Lady Susan Ramsay (1837-1898), the elder daughter of the Marquess of Dalhousie, Governor-General of India from 1848 to 1856. The correspondence was written over a two-year period: commencing with Susan's positive response to her father's request that she join him in Calcutta, following the death of her mother; and concluding with Susan's arrival with her father at Southampton. Lady Susan was still only 17 when she arrived in India, and was therefore the youngest person to take up the role of vicereine of India. Her letters and journal represent the unique viewpoint of a highly intelligent, witty, articulate and unprejudiced young woman expressed from locations that range from Osborne on the Isle of Wight to Seringapatam in Mysore. The detail, maturity and inventive quality of her writing invites comparison with that of Emily Eden, Emily Metcalfe, Charlotte Canning and other prominent early Victorian women. Accompanied by extensive introductions and annotations by Ross Nelson, this volume will be of great interest to students and scholars of Imperial History.